Po poti klinične farmacije na Kliniki Golnik - Knez, Lea (Farmacevtski vestnik, 2018)
The beginnings of clinical pharmacy at the University clinic Golnik date back to the year 2004. Herein the developments that led to the recognition of clinical pharmacists as a member of the healthcare team and their integration in routine patient care are described. Special emphasis is put on the role of research activities throughout the implementation of clinical pharmacy services. Clinical pharmacy services should be well-defined and regularly provided, focusing on patients at high risk for serious adverse drug events and tackling problems where clinical pharmacists' expertise is most needed. Nevertheless, clinical pharmacy services should be well integrated into routine clinical practice and accepted by other healthcare professionals in order to achieve their final goal: optimising patient care.
Keywords: Farmacevti; Klinična farmacija; Klinika Golnik; neželeni dogodki; sistemsko zdravljenje raka; usklajevanje zdravljenja z zdravili; zdravljenje z zdravili